Early embryonic development in the tick Ixodes scapularis suggests syncytial organization and cellularization before blastoderm formation - Isaac A. Hinne; Hailee R. Ciccotti; Jakub Wudarski; Michael N. Pham; Arvind Sharma; Molly M. McVicar; Benjamin Faustino; Andrew B. Nuss; Prashant P. Sharma; Monika Gulia-Nuss (EvoDevo)
Abstract Ixodes ticks are the most important vectors of arthropod-borne diseases in the United States, Canada, and Europe. Ixodes scapularis is the major vector that transmits the causative agent of Lyme disease in the eastern United States and can transmit up to six additional pathogens. In recent years, many advances have been made in building the toolkit for I. scapularis research, including genomic resources, transcriptomes, and forward and reverse genetics techniques. However, an understanding of the early embryonic development of this species is still lacking. In this study, we attempted to fill this knowledge gap and to further the efforts of functional genomics tools development. We developed a staging system consisting of 16 (0–15) stages describing unique morphologies and used wheat germ agglutinin staining and fluorescent dye injections to confirm cell membrane formation. These results provide an opportunity to identify an ideal time window for tick transgenics and deepen our understanding of the events during embryo development.